Katherine M. D. Dunbabin: The Roman Banquet: Images of Conviviality & Matthew Roller: Dining Posture in Ancient Rome: Bodies, Values, and Status - Dalby, Andrew (Petits Propos Culinaires, 2007)
Katherine M. D. Dunbabin: The Roman Banquet: Images of Conviviality: Cambridge University Press, 2003: ISBN 0521822521: £59. Matthew Roller: Dining Posture in Ancient Rome: Bodies, Values, and Status: Princeton University Press, 2006: ISBN 0691124574: £26.95